The role of Jewish scientific families in the translation and transfer of science from Andalusia to Europe (4-9 Ah / 10-15 ad) - djelti, souad; si-abdelkader, omar (The Algerian Historical Journal, 2026)
The subject of the research is the role of Jewish scientific families in the translation and transfer of knowledge and science from Andalusia to Europe during the period from the 4th-9th century AH / 10-15th ad, through the translation movement in Andalusia and the schools that were founded to translate Muslim literature and the work of Jews in them, especially as they have great knowledge of the languages of Arabic and Latin, as a result of their mixing and coexistence with Muslims .we have touched on the role played by Jews in the translation movement and the transit of literature to Europe and focused on the examples of the most important Jewish scientific families involved in translation.